In it to win it - Cooper, Sharon C. (Berkley Romance, 2022)
"Spoiled, fickle, and prissy are only a few adjectives that have been used to describe Morgan Redford. Though she's never had to worry about money, she's determined to make a name for herself on her own terms. Her new venture won't be an epic fail like her former professional cuddling service or the pet hotel that never got off the ground. No, through the nonprofit she founded, Morgan is doing something meaningful--helping teens who are aging out of the foster care system--and she's got her eye on a property that could house these kids. But the competition is steep, and one of the bidders is someone she never expected... When Los Angeles real estate developer Drake Faulkner learns that his eccentric mentor is selling property that is a part of Drake's legacy, he jumps at the chance to buy it. But he soon learns the billionaire has other ideas: buyers must compete in an Iron Man competition of sorts for the property. Drake refuses to play along with this ridiculous demand... until he finds out Morgan, his ex who ghosted him years ago, is one of the potential buyers. No way is he letting her--Little-Miss-Can't-Run-A-Block-Without-Gasping-For-Air--win the property he wants. Bitter? Yes. Petty? Probably. But as the gauntlet of games heats up and forces them to face the past, they are met with a pull that feels all too familiar. Now, if they could only keep their eyes on the prize and off each other--but who's to say they can't do both?"--